THE ROLE OF SUBJECTIVE NORM IN EXPLAINING JAWI ADOPTION AMONG INDIANS IN MALAYSIA - Nor Fadzilah bt Md Yusof; Mohd Khairul Bin Abdul Ghani; Nur Aulia Fahada binti Misaridin; Wan Hashridz Rizal bin Wan Abu Bakar2, (Journal of Islamic, Social, Economics and Development, 2021)
Jawi is the orthography used to write Malay since the Middle Ages, when it was adapted from the Arabic script. It was introduced by Muslim traders and adapted to Malay phonology by using diacritics that changed six letters. After the Malaysian government announced a plan to introduce jawi script at the basic level for Primary Four vernacular school pupils beginning 2020, the issue has fueled tension among educationists, school officials, and the general public. Therefore, this study aims to identify the role of subjective norms in explaining the intention to Jawi adoption among Indian community in Malaysia. This study was conducted with a total of 192 respondents. The sampling technique used is non-probability sampling. The findings of the study prove that subjective norms has a positive and significant relationship with the intention to Jawi adoption among Indian in Malaysia.